RACISM IN THE FORM OF SILENT VIOLENCE AND THE CONTRIBUTIONS OF INSTITUTIONAL PEDAGOGY IN ITS FIGHT - Tarcia Regina da Silva; Adelaide Alves Dias (Editora da Universidade de Santa Cruz do Sul, 2013)
This study contextualizes violence within schools, pausing in his expression as symbolic. Symbolic violence is present so subtle that many times we do not realize its impact. Living in a country where hangs the myth of racial democracy, combating racism is also reflect on our own values, beliefs and behaviors. Thus, consisting of Institutional Pedagogy see, add and manage conflict breaks the silence of racism in school, favoring his match through its theoretical foundations. This text highlights the possibilities presented by the Institutional Pedagogy to combat racial discrimination in school that children, youth, adults and seniors are objects. So we can say that the Institutional Pedagogy presents itself as a possibility of mediation to build a society with social justice, the place where the threshold, law and language lead to a land of fairness and respect.